Biodiversity screening of gut microbiome during the allogeneic hematopoietic stem cell transplantation: data from the real-life clinical practice. Issue 1 (31st December 2022) - Stoma, Igor; Uss, Mikhail; Milanovich, Natalia; Stoma, Valentina; Gubanova, Tatiana; Moduleva, Ekaterina; Iskrov, Igor; Uss, Anatoly
Abstract : Biodiversity of a gut microbiome has been shown as an important predictor of transplant-related outcomes and infections in allogeneic hematopoietic stem cell transplantation (HSCT). We conducted a single-center real-life clinical study and implemented a routine gut microbiome diversity monitoring across the course of allogeneic HSCT. Twelve patients (with ALL, AML, CML, biphenotypic leukemia and aplastic anemia) were enrolled in a stool samples collection protocol before the start of HSCT and during a 30-day post-transplant period. We have shown the feasibility of a gut microbiome monitoring in a real-life clinical setting and have proven that the alpha-biodiversity of the microbiome is significantly reduced with HSCT in comparison with the individual patient baseline level (Xdc 72.93; p < 0.001; multivariate Dirichlet analysis), what may be related to the antibiotic use and conditioning regimen. Overall, the gut microbiome biodiversity monitoring may be clinically used in a real-life HSCT setting to identify the high-risk groups for developing bloodstream infections and transplant-related negative outcomes.